Female membrane proteins regulate postmating ovulation in Drosophila melanogaster by ovulin-dependent and -independent pathways - Mengye Yang; Melissa A. White; Geoffrey D. Findlay; Ryan C. Vignogna; Jennifer Apger-McGlaughon; Nathan L. Clark; Jae Young Choi; J. Christopher Fromme; Mariana F. Wolfner (Proceedings of the National Academy of Sciences, 2025)
Ovulation is an intricate process that is essential for reproductive success. In Drosophila melanogaster , ovulation increases after mating. This increase is initiated by the male seminal fluid protein ovulin and is executed by female pathways, including octopamine (OA) neuronal signaling. Despite OA signaling’s central role in ovulation regulation, the broader molecular landscape underlying female control of ovulation remains poorly understood. Here, using ovulin as a probe, we performed evolutionary rate covariation and AlphaFold-Multimer prediction screens to identify candidate female ovulation-regulating proteins. Ovulation assays performed on knockdowns or mutants of identified membrane-protein candidates revealed seven important female ovulation regulators: Lgr3, GabaβR1, SIFaR, mthl9, Smog, Cirl, and CG6067. Lgr3 and GabaβR1 function in an ovulin-dependent manner, while SIFaR and mthl9 regulate ovulation independently of ovulin. For proteins with known nervous system expression, we examined their requirement in OA neurons and their expression in female reproductive tract neurons. Tissue-specific knockdown revealed that Lgr3, GabaβR1, SIFaR, and CG6067 act in OA neurons to influence ovulation, highlighting OA neurons as a key signaling hub. Additionally, Lgr3, GabaβR1, SIFaR, Smog, and Cirl are expressed in OA neurons innervating the reproductive tract, suggesting a potential local function. Finally, we identified evidence of recurrent positive selection having acted on residues within Smog’s ligand binding region, which is interesting in light of ovulin’s rapid evolution. Together, these findings significantly expand our understanding of the molecular networks regulating ovulation following mating in Drosophila .